A Novel Approach to Support Scalable Multicast Routing in Wireless Ad Hoc Networks - Qabajeh, Mohammad M. (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Nowadays, group communications over Mobile Ad hoc Networks (MANETs) have received significant attention. Multicasting plays an important role in simultaneous delivery of information to group of receivers. Thus, it is necessary to design efficient and effective multicast routing protocol to support group communication applications. Several efforts have been put to improve multicast routing. However, they do not consider scalability issue. This paper introduces a a novel Scalable Geographic Multicast Routing Protocol (SGMRP). The main objective of this protocol is to design a lightweight scalable multicast routing scheme irrespective of the number of multicast members and network size. To achieve this, a virtual clustering strategy has been introduced. This strategy based on partitioning the network into sectorial zones. The proposed solution performs efficient packet forwarding with reduced communication overhead. The proposed scheme eliminates the duplicate packets between clusters and reduces the number of participating nodes